Reactive Sintering Mechanism and Phase Formation in Ni-Ti-Al Powder Mixture During Heating - Salvetr, Pavel; Školáková, Andrea; Hudrisier, Cyprien; Novák, Pavel; Vojtěch, Dalibor (Materials (Basel, Switzerland), 2018)
This work aims to describe the formation of intermetallics in the Ni-Ti-Al system in dependence on the heating rate, which has been determined previously as the crucial factor of thermal explosion self-propagating synthesis (TE-SHS). The tested alloys contained 1⁻7 wt % aluminum. Thermal analysis has been realized by the optical pyrometer under the conditions of high heating rates up to 110 °C·min−1. TE-SHS process in Ni-Ti-Al system is initiated by exothermic reaction of nickel aluminides Ni₂Al₃ and NiAl₃ at the temperature of 535⁻610 °C. The next reactions occur in dependence on the heating rate. Samples containing 1⁻3 wt % of aluminum exhibit the similar initiation temperature as Ni-Ti binary mixture. The samples containing 5 wt % and more of aluminum were fully reacted after sintering at 800 °C with the heating rate of 300 °C·min−1 and the initiation temperature of the TE-SHS was observed close to Al-Al₃Ni eutectic temperature (between 630⁻640 °C).
Keywords: Ni-Ti-Al alloy; intermetallics; differential thermal analysis; self-propagating high-temperature synthesis (SHS); reactive sintering